Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 1)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 1)" [g0973001.jpg], n.d.